2021
DOI: 10.3390/ijms23010386
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation in Retinal Neurodegeneration and Degenerative Diseases

Abstract: Retinal neurodegeneration is predominantly reported as the apoptosis or impaired function of the photoreceptors. Retinal degeneration is a major causative factor of irreversible vision loss leading to blindness. In recent years, retinal degenerative diseases have been investigated and many genes and genetic defects have been elucidated by many of the causative factors. An enormous amount of research has been performed to determine the pathogenesis of retinal degenerative conditions and to formulate the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 158 publications
1
30
0
Order By: Relevance
“…Of note, red blood cells were virtually absent in all the samples evaluated, thus excluding blood contamination. Therefore, our data support the hypothesis of a role of in ammation in the pathogenesis of RP, in agreement with literature (23) Interestingly, the cell composition of AH was limited to MNCs; moreover, lymphocyte composition was different from that found in the blood sample of the same patients, with a signi cant reduction of NK cells, of CD4 + Th cells and with a signi cant increase of CD3 + CD4-CD8-T cells, mainly made up of TCRαβ lymphocytes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of note, red blood cells were virtually absent in all the samples evaluated, thus excluding blood contamination. Therefore, our data support the hypothesis of a role of in ammation in the pathogenesis of RP, in agreement with literature (23) Interestingly, the cell composition of AH was limited to MNCs; moreover, lymphocyte composition was different from that found in the blood sample of the same patients, with a signi cant reduction of NK cells, of CD4 + Th cells and with a signi cant increase of CD3 + CD4-CD8-T cells, mainly made up of TCRαβ lymphocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the corneal endothelium and retina do not express the Major histocompatibility complex (MHC) class I molecules and are a potential target of cytotoxic activity by NK cells; this could represent the starting point or the progression of an in ammatory condition. It has been shown that the aqueous humour contains a wide range of soluble factors inhibiting immune response, in particular NK-mediated cytotoxicity, the main being represented by TGF-b (23,24). We could speculate that the ocular micro-enviroment contributes to reducing the frequency of NK cells in order to maintain tissue protection and support the immunological privilege.…”
Section: Discussionmentioning
confidence: 98%
“…The various harmful stimuli are detected by retinal immune cells through engagement with pattern recognition receptors, including pathogen-associated molecular patterns and damage-associated molecular patterns, which respond by upregulating myriad inflammatory genes [ 25 ]. Four classes of pathogen recognition receptor families have been described to date: Toll-like receptors, C-type lectin receptors, retinoic acid-inducible gene (RIG)-I-like receptors, and NOD-like receptors [ 26 ].…”
Section: Definition Of Oxidative Stress and Inflammationmentioning
confidence: 99%
“…Similar to other degenerative CNS diseases, the major contributors to IRD-related inflammation and cell death are TNF-𝛼 and interleukin (IL)-1. TNF-𝛼 is a key factor secreted in the retina by activated microglia and macrophages [ 25 ] and can trigger different cell-death mechanisms, including apoptosis, pyroptosis, necroptosis, and parthanatos [ 25 , 28 ].…”
Section: Definition Of Oxidative Stress and Inflammationmentioning
confidence: 99%
“…Zebrafish possess tremendous intrinsic regenerative potential in ocular tissues, including the retinal pigment epithelium (RPE), while mammalian RPE is limited in its regenerative capacity. RPE inflammatory events highly participate in neurodegenerative progress, and RPE dysfunction or disease can lead to blindness in humans [ 16 ]. Of interest, macrophage/microglia cells have been recently shown to be responsive to RPE damage in zebrafish, and their function is required for the timely progression of the RPE regenerative response [ 17 ].…”
Section: Alternative Organism Models For Retina Neuroregenerationmentioning
confidence: 99%